Letramentos queer na formação de professorxs de línguas: complicando e subvertendo identidades no fazer docente - Freitas, Marco Túlio de Urzêda (2018)
This research aims at investigating the consequences of an experience with queer literacies in the field of language teacher education. Supported by premises of queer theories, literacy studies and critical teacher education, I understand queer literacies as social practices of language use turned to the queering of the dichotomies related to the body, identities and social life in the teacher’s practice. The empirical materials were generated in the meetings of the course Questões de Gênero e Sexualidade no Ensino de Línguas Estrangeiras/Adicionais, conducted by me at the Centro de Línguas of the Universidade Federal de Goiás throughout 2013. Divided into two phases, this course aimed at problematizing the concepts of identity, gender and sexuality in the contemporary world, as well as relating such concepts to language teaching, identifying possibilities for the implementation of queer interventions in different educational contexts. The study is presented as a queer-decolonial research about literacies, as its methodological procedures point to a series of micro-ruptures with colonial standards of knowledge production, especially regarding the epistemological basis of the research, the way its tools were comprehended and used throughout the study, and the relationship between the researcher and the articulators with the reality under analysis. Based on the empirical materials generated through my research diary, a questionnaire, the texts written by the articulators, two reflections about the course, the queer interventions proposed and the final essay produced by the articulators, I intend to reflect on the following questions: How do the articulators comprehend the relations of gender and sexuality in the contemporary world? How do the articulators perform their gender, sexual, and other identities in the discursive practices of the group? How do the articulators relate the academic theories focused on the course to their respective practices? The reflections on these questions make it possible to infer that, despite the complexities that constitue the implementation of queer literacies in contexts marked by inherited conceptions of identity and knowledge, a teacher education experience with queer literacies offer meaningful conditions for teachers to engaje in the making of projects that aim at the queering of the Eurocentric, binary, and colonial character of the official school literacy, creating new repertories and new performances for the teacher’s practice in the field of language teaching.